Foliar application of chitosan-putrescine nanoparticles (CTS-Put NPs) alleviates cadmium toxicity in grapevine (Vitis vinifera L.) cv. Sultana: modulation of antioxidant and photosynthetic status - Panahirad, Sima; Gohari, Gholamreza; Mahdavinia, Gholamreza; Jafari, Hessam; Kulak, Muhittin; Fotopoulos, Vasileios; Alcázar, Rubén; Dadpour, Mohammadreza (My University, 2023)
Cadmium (Cd) stress displays critical damage to the plant growth and health. Uptake and accumulation of Cd in plant tissues cause detrimental effects on crop productivity and ultimately impose threats to human beings. For this reason, a quite number of attempts have been made to buffer the adverse effects or to reduce the uptake of Cd. Of those strategies, the application of functionalized nanoparticles has lately attracted increasing attention. Former reports clearly noted that putrescine (Put) displayed promising effects on alleviating different stress conditions like Cd and similarly chitosan (CTS), as well as its nano form, demonstrated parallel properties in this regard besides acting as a carrier for many loads with different applications in the agriculture industry. Herein, we, for the first time, assayed the potential effects of nano-conjugate form of Put and CTS (CTS-Put NP) on grapevine (Vitis vinifera L.) cv. Sultana suffering from Cd stress. We hypothesized that their nano conjugate combination (CTS-Put NPs) could potentially enhance Put proficiency, above all at lower doses under stress conditions via CTS as a carrier for Put. In this regard, Put (50 mg L- 1), CTS (0.5%), Put 50 mg L- 1 + CTS 0.5%" and CTS-Put NPs (0.1 and 0.5%) were applied on grapevines under Cd-stress conditions (0 and 10 mg kg- 1). The interactive effects of CTS-Put NP were investigated through a series of physiological and biochemical assays.
Keywords: Abiotic stress; Carrier; Heavy metal; Horticultural crop; Nanoparticles; Toxicity